Strength training of junior biathletes - Ivanov, D. I.; Gorbunov, S. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to assess the feasibility and effectiveness of introduction of strength mesocycles in the process of training of junior biathletes. Methods and structure of the study. The practical part of the experiment involved 12 junior biathletes of 14-15 years of age (I-II sports category). The Control Group was made of 20 athletes of the same qualification and age. They were trained without the inclusion of strength mesocycles. The trainings and testing were carried out on the basis of Tchaikovsky State Institute of Physical Culture. At the beginning of the preparatory period, the training cycle was broken down into 2 mesocycles. The first one took on the task of increasing the oxidizing potential in the transitional muscle fibers and, partly, hypertrophy of oxidizing muscle fibers. The second one took on the task of building up the power potential in the oxidizing and transitional muscle fibers, while preserving the desired muscle properties. Results of the study and conclusions. During the experimental part, we observed a significant increase of indicators not only in the exercises that characterize strength fitness, which is natural, but also in the exercises that help evaluate technical, tactical and integral fitness. The latter seems to be especially important, since the degree of influence of the basic component on the athletes` conditional competitive fitness was obvious. The greatest increment in the results was observed in the aerobic exercises: "Clamshell Exercise" - 18.5%, "Dip-ups with rear support" - 15.6%, "Vertical jump with a squat (for 1 min)" - 21, 8%, "Wall slide" with the loading of 15% of the body weight - 14%. The inclusion of strength-building blocks (2 mesocycles) in the process of training of junior biathletes, which improved the oxidizing ability of transitional muscle fibers, and power potential of oxidizing fibers not only improved the strength characteristics, but also contributed to an increase in the results when performing imitation and competitive exercises. We assume with a high degree of probability that the inclusion of strength mesocycles will positively affect the competitive results.